Theory and practice of internationalization of universities in the context of global challenges of the time - Кошербаева, Айгерим; Исалиева, Сауле; Мусабекова, Гульвира (Pedagogy and Psychology, 2020)
The article discusses the problems of integration of Kazakhstan into the world educational environment and one of the main trends of globalization – the internationalization of education. In accordance with the State Program for the Development of Education and Science, an analysis of universities that provide educational services to foreign students is carried out, criteria for foreign universities and the Register of Kazakhstan’ universities are created. An overview of the factors and global trends, the main country approaches and concepts, the Strategy and the Internationalization Roadmap is given, the difference between them is indicated and the competitive advantages of Kazakhstan, which has the necessary quality of education, as well as the complexity and dynamism of the internationalization process, are shown. The following is the main content of the project “Theory and practice of internationalization of universities in he context of global challenges of the time”, which covers all possible areas of activity in this area.